2012
DOI: 10.1097/ico.0b013e318243f6b1
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond-Assisted Keratopigmentation Double Tunnel Technique in the Management of a Case of Urrets-Zavalia Syndrome

Abstract: A femtosecond-assisted keratopigmentation technique using 2 pigmented intrastromal tunnels to achieve an intracorneal pigmented replica of the iris was effective in improving the patient's severe visual function disability and cosmetic appearance. To the best of our knowledge, this is the first report of severe visual function disability caused by atrophic iris and a fixed dilated pupil treated with double intrastromal layers of keratopigmentation by means of femtosecond-created tunnels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…The good outcomes found, the high safety profile with lack of toxicity, tolerance to pigments of modern KTP found in our investigations, and positive patient satisfaction [8][9][10] encouraged us to seek a novel indication, which is elective cosmetic KTP in adequately selected patients who wish to change the color of their eyes to acquire a much desired cosmetic appearance. We report the outcomes of our first 7 cases of purely cosmetic KTP.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The good outcomes found, the high safety profile with lack of toxicity, tolerance to pigments of modern KTP found in our investigations, and positive patient satisfaction [8][9][10] encouraged us to seek a novel indication, which is elective cosmetic KTP in adequately selected patients who wish to change the color of their eyes to acquire a much desired cosmetic appearance. We report the outcomes of our first 7 cases of purely cosmetic KTP.…”
mentioning
confidence: 77%
“…6 The second is the functional therapeutic, to treat debilitating visual symptoms such as light scattering, photophobia, or incapacitating diplopia, caused by cases of iris defects, such as posttraumatic aniridia or iris coloboma. [7][8][9][10][11] The use of KTP in these indications waives the need for other more complex or risky surgical procedures such as evisceration, enucleation, or penetrating keratoplasty, and the frequent problem of poor tolerance to using cosmetic colored contact lenses.…”
mentioning
confidence: 99%
“…Some authors have suggested femtosecond-assisted keratopigmentation to create the lamellar pockets and facilitate the technique in human eyes, achieving predictable configuration and distribution of the pigments in the stroma 11 13…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the tolerance and biocompatibility of micronised mineral pigments for KTP,1 12 13 16 17 the aim of our study is to investigate in an experimental animal model the potential of corneal tattooing using these pigments for cosmetic reasons. We also sought to demonstrate the safety, tolerance and medium-term durability of this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The following KTP techniques were used: superficial automated keratopigmentation (SAK),6 femtosecond-assisted keratopigmentation (FAK) using a single tunnel technique4 6 13 or a double tunnel technique5 and manual intralamellar keratopigmentation (MIK) 6 14–16…”
Section: Methodsmentioning
confidence: 99%